Investigation of the Brain Biodistribution of the Lipoprotein-Associated Phospholipase A(2) (Lp-PLA(2)) Inhibitor [(18)F]GSK2647544 in Healthy Male Subjects - Huiban, Mickael (Mol Imaging Biol, 2016)
PURPOSE: GSK2647544 is a potent and specific inhibitor of lipoprotein-associated phospholipase A(2) (Lp-PLA(2)), which was in development as a potential treatment for Alzheimer’s disease (AD). In order to refine therapeutic dose predictions and confirm brain penetration, a radiolabelled form of the inhibitor, [(18)F]GSK2647544, was manufactured for use in a positron emission tomography (PET) biodistribution study. PROCEDURES: [(18)F]GSK2647544 was produced using a novel, copper iodide (Cu(I)) mediated, [(18)F]trifluoromethylation methodology. Healthy male subjects (n = 4, age range 34–42) received an oral dose of unlabelled GSK2647544 (100 mg) and after 2 h an intravenous (iv) injection of [(18)F]GSK2647544 (average injected activity and mass were 106 ± 47 MBq and 179 ± 55 μg, respectively) followed by dynamic PET scans for 120 min. Defined regions of interest (ROI) throughout the brain were used to obtain regional time-activity curves (TACs) and compartmental modelling analysis used to estimate the primary outcome measure, whole brain volume of distribution (V(T)). Secondary PK and safety endpoints were also recorded. RESULTS: PET dynamic data were successfully obtained from all four subjects and there were no clinically significant variations of the safety endpoints. Inspection of the TACs indicated a relatively homogenous uptake of [(18)F]GSK2647544 across all the ROIs examined. The mean whole brain V(T) was 0.56 (95 % CI, 0.41–0.72). Secondary PK parameters, C(max) (geometric mean) and T(max) (median), were 354 ng/ml and 1.4 h, respectively. Metabolism of GSK2647544 was relatively consistent across subjects, with 20–40 % of the parent compound [(18)F]GSK2647544 present after 120 min. CONCLUSIONS: The study provides evidence that GSK2647544 is able to cross the blood brain barrier in healthy male subjects leading to a measurable brain exposure. The administered doses of GSK2647544 were well tolerated. Exploratory modelling suggested that a twice-daily dose of 102 mg, at steady state, would provide ~80 % trough inhibition of brain Lp-PLA(2) activity. TRIAL REGISTRATION: Clintrials.gov: NCT01924858. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11307-016-0982-5) contains supplementary material, which is available to authorized users.